ANALISIS DAYA MINAT PENGUNJUNG TERHADAP WISATA ALAM AIR TERJUN DENALO MARAS KECAMATAN BATANG CENAKU KABUPATEN INDRAGIRI HULU PROVINSI RIAU - Putra, Ade Eka; Yoza, Defri; M. Mardhiansyah, M. Mardhiansyah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Denalo Maras Waterfall located in Batang Cenaku District in Alim village. Denalo Maras offers the beautiful nature scenery like forest and the twin of waterfall that flow in one place. This research aims to determine the perception of society and the interest of visitors toward of Waterfall Denalo Maras Batang Cenaku District Indragiri Hulu regency Riau Province. This research used the observation method, quisioner and references study. The result of this research showed that the interests of society to waterfall Denalo Maras still have of high percentage that is 90,52% of 38 visitors that visited this waterfall. The visitors give some expression like environment, beautifull scenery and comfortable when visit this place. The result of this research showed that visitors feel this location very clean with the percentage 94,74% visitors says beautifull scenary with the percentage 97,37% and the comfortable place is 100,00%.Keywords: Interest, Denalo Maras Waterfall, Batang Cenaku